Perencanaan Struktur Gedung Kampus 5 Lantai Dengan Metode Daktail Parsial Di Wilayah Gempa 3 - Priatama, Tityo, Ir. Abdul Rochman, M.T, Basuki, S.T., M.T (2015)
Building structure planning have to be planned properly with the building planning guide that have been decided in order to reach the factor of strength and security, so that the collapse of the building will never happen as prepared in the planning. So that the hold building structure planning of 5 floors campus using partial ductile method in the earthquake area 3 is related to the Planning Guide of Concrete Structure for Building (SNI 03-2847-2002). This building is planned to be build in the earthquake area 3 which consists of hard soil partial ductile system with the value of ductility (μ) = 5 and the factor of earthquake reduction (R) = 8,0. The planning of the building structure covers upper structure and bellow structure. Upper structure covers about roof planning (easel) and reinforced concrete (floor plate, ladder, beam, and column), thus the below structure covers foundation structure. In analyzing building structure is applied "SAP 2000 v.14" computer program in order to ease and increase in counting. In the other hand the drawing of the planning is using AutoCAD v.2014 program. The quality of concrete and steel of reinforced concrete is fc' = 25 MPa, main reinforcement fy = 400 MPa and shear reinforcement fy = 240 MPa. Besides, for the easel steel is using Bj 37 steel quality class with the yield stress = 250 MPa and the basic stress is 160 Mpa. The foundation is using pilling with the depth about 6 metres. The result of the building structure planning are : easel frame structure using 2L 50.50.5, and 2L 30.30.5 profile, using welding tool and 10 mm cusset plate. The thickness of roof plate is 10 cm with the main reinforcement D10 and the divider reinforcement D8. The thickness of floor plate is 12 cm with the main reinforcement D10 and the divider reinforcement D8. The thickness of ladder plate and bordes are 12 cm with the main reinforcement D16 and divider reinforcement D8. The main beam is using 400/600 dimension, and planning column is using 600/600 dimension. The dimension of the piling is 400/400 mm with the main reinforcement D19 and shear reinforcement 2 dp 6, the poer plate thickness of (3x3) m2 is about 0.8 m with the main reinforcement D22 and divider reinforcement D16, in the other hand the sloof dimension of 350/500 is using main reinforcement D16 and shear reinforcement 2 dp 10.